FOXO1 Regulates Bacteria-Induced Neutrophil Activity - Dong, Guangyu; Song, Liang; Tian, Chen; Wang, Yu; Miao, Fang; Zheng, Jiabao; Lu, Chanyi; Alsadun, Sarah; Graves, Dana T. (Frontiers in Immunology, 2017)
Neutrophils play an essential role in the innate immune response to microbial infection and are particularly important in clearing bacterial infection. We investigated the role of the transcription factor FOXO1 in the response of neutrophils to bacterial challenge with Porphyromonas gingivalis in vivo and in vitro. In these experiments the effect of lineage-specific FOXO1 deletion in LyzM.Cre+FOXO1L/L mice was compared with matched littermate controls. FOXO1 deletion negatively affected several critical aspects of neutrophil function in vivo including mobilization of neutrophils from the bone marrow to the vasculature, recruitment of neutrophils to sites of bacterial inoculation and clearance of bacteria. In vitro FOXO1 regulated neutrophil chemotaxis and bacterial-killing. Moreover, bacteria-induced expression of CXCR2 and CD11b, which are essential for several aspects of neutrophil function was dependent on FOXO1 in vivo and in vitro. Furthermore, FOXO1 directly interacted with the promoter regions of CXCR2 and CD11b. Bacteria-induced nuclear localization of FOXO1 was dependent upon TLR2 and/or TLR4 and was significantly reduced by inhibitors of reactive oxygen species (ROS and NOS) and deacetylases (Sirt1 and HDAC). These studies show for the first time that FOXO1 activation by bacterial challenge is needed to mobilize neutrophils to transit from the bone marrow to peripheral tissues in response to infection as well as for bacterial clearance in vivo. Moreover, FOXO1 regulates neutrophil function that facilitates chemotaxis, phagocytosis and bacterial killing.